Community Involvement in Health Systems Strengthening to Improve Global Health Outcomes: A Review of Guidelines and Potential Roles. (July 2017) - Sacks, Emma; Swanson, Robert C.; Schensul, Jean J.; Gleave, Anna; Shelley, Katharine D.; Were, Miriam K.; Chowdhury, A. Mushtaque; LeBan, Karen; Perry, Henry B.
Definitions of health systems strengthening (HSS) have been limited in their inclusion of communities, despite evidence that community involvement improves program effectiveness for many health interventions. We review 15 frameworks for HSS, highlighting how communities are represented and find few delineated roles for community members or organizations. This review raises the need for a cohesive definition of community involvement in HSS and well-described activities that communities can play in the process. We discuss how communities can engage with HSS in four different areas—planning and priority-setting; program implementation; monitoring, evaluation, and quality improvement; and advocacy—and how these activities could be better incorporated into key HSS frameworks. We argue for more carefully designed interactions between health systems policies and structures, planned health systems improvements, and local communities. These interactions should consider local community inputs, strengths, cultural and social assets, as well as limitations in and opportunities for increasing capacity for better health outcomes.